Penyuluhan Pengembangan Good Character Bagi Siswa SMK. Zainul Hasan Genggong Kabupaten Probolinggo - Hifdil Islam, Muhammad; Tri Wisudaningsih, Endah (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
Abstract: In this study the authors wanted to know: the values ​​of character, supporting and inhibiting factors in the cultivation of character values ​​Zainul Hasan Genggong vocational students. This study used a qualitative approach to phenomenology. Collecting data using interview techniques, observation, and documentation. Data analysis was performed using the interactive analysis model of Miles & Huberman. The results showed; 1) The values ​​instilled in vocational Genggong is Zainul Hasan Islamic character values ​​based boarding school; 2) The process of planting the values ​​of character education in vocational Zainul Hasan Genggong through the context of micro and macro context. Micro context: the integration of the value of the character with each subject and local content, school culture, and self-development activities. Macro context: family, school and community; and 3) supporting and pengambat factors: (a) the supporting factors: SMK have adequate human resources, the majority of students in the boarding school, the existence of synergy between the family, school, and community. (B) inhibiting factors: lack of infrastructure, understanding differences, the lack of a boarding school, public apathy towards the boarding school-based vocational.Keywords: Character Education, Islamic Boarding School